1990
DOI: 10.1164/ajrccm/142.5.1004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Distal Bronchial Microflora during Acute Exacerbation of Chronic Bronchitis: Use of the Protected Specimen Brush Technique in 54 Mechanically Ventilated Patients

Abstract: To obtain accurate information on distal bronchial microflora during acute exacerbation in patients with chronic bronchitis, we prospectively studied 54 such patients who had been receiving mechanical ventilation because of hypercapnic respiratory failure. Fiberoptic bronchoscopy using a protected specimen brush (PSB) was performed on each patient within the first 24 h after admission. Cultures of protected brush specimens demonstrated no growth in 27 patients (50%). With the exception of fever (38.2 +/- 0.8 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
22

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(120 citation statements)
references
References 7 publications
4
92
1
22
Order By: Relevance
“…The limitations of sputum culture include methodological issues regarding sputum processing, culture techniques, contamination of the upper airway, and colonization. Bronchoscopic studies have confirmed that PPM are identified in many patients with stable COPD and during AECOPDs (38)(39)(40)(41). Two bronchoscopic studies have related the identification of PPM in bronchoalveolar lavage with increased markers of predominantly neutrophilic inflammation (36,42).…”
Section: Transatlantic Airway Conferencementioning
confidence: 90%
“…The limitations of sputum culture include methodological issues regarding sputum processing, culture techniques, contamination of the upper airway, and colonization. Bronchoscopic studies have confirmed that PPM are identified in many patients with stable COPD and during AECOPDs (38)(39)(40)(41). Two bronchoscopic studies have related the identification of PPM in bronchoalveolar lavage with increased markers of predominantly neutrophilic inflammation (36,42).…”
Section: Transatlantic Airway Conferencementioning
confidence: 90%
“…Bronchoscopically collected samples have confirmed that potentially pathogenic microorganisms are identified in many patients with COPD at baseline and during AE-COPDs (74)(75)(76)(77)(78). A recent review pooled data from six published studies suggesting that there was a clear shift to organisms with a higher pathogenic potential (79).…”
Section: Bacteriamentioning
confidence: 96%
“…Studi broncoscopici hanno mostrato che almeno il 50 % dei pazienti presentano batteri nelle vie aeree distali durante la riacutizzazione della BPCO (192), ma una significativa proporzione di questi pazienti sono colonizzati dai batteri anche nelle fasi di stabilità della malattia. D'altra parte, ci sono dei dati che indicano un aumento della carica batterica durante la riacutizzazione della BPCO (193).…”
Section: In Ospedaleunclassified